Three-dimensional computer-guided implant placement in oligodontia - Filius, Marieke A. P. (Int J Implant Dent, 2017)
BACKGROUND: The aim of computer-designed surgical templates is to attain higher precision and accuracy of implant placement, particularly for compromised cases. PURPOSE: The purpose of this study is to show the benefit of a full three-dimensional virtual workflow to guide implant placement in oligodontia cases where treatment is challenging due compromised bone quantity and limited interdental spaces. PATIENT AND METHODS: A full, digitalized workflow was performed for implant placement in two oligodontia patients. Accuracy was assessed by calculating the coordinates of the entry point (shoulder) and apex (tip) as well as the angular deviation of the planned and actual implants. RESULTS: Implant placement could be well performed with the developed computer-designed templates in oligodontia. Mean shoulder deviation was 1.41 mm (SD 0.55), mean apical deviation was 1.20 mm (SD 0.54) and mean angular deviation was 5.27° (SD 2.51). CONCLUSION: Application of computer-designed surgical templates, as described in this technical advanced article, aid in predictable implant placement in oligodontia where bone quantity is scarce and interdental spaces are limited.